(untitled) (Journal of Information Technologies in Education (ITE), 2014)
To improve the training process is necessary to use such powerful technologies, as ‘cloud computing’. Supporting traditional training forms, it’s the new epoch of education development. It’s also economic, effective and flexible way to satisfy the needs of taught in new knowledge getting.